2023
DOI: 10.1017/s1047951123000136
|View full text |Cite
|
Sign up to set email alerts
|

Do quantitative levels of cardiac troponin I implicate on severity of disease in children, adolescences, and young adults with acute myocarditis and myopericarditis?

Abstract: Objectives: When cardiac muscle damage occurs, cardiac troponins are released to blood and their detection is used as a marker in clinical setting. The prognostic value of the quantitative levels of blood troponin I in cases of myocarditis and myopericarditis is unclear. The aim of this study was to analyse whether troponin quantitative blood levels can be correlated with the course of hospitalisation and prognosis. Methods: Retrospective data was collected from all consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Based on CDC guidance, troponin elevation is an integral part of the diagnosis of myocarditis and may also be used to chart clinical improvement [64]. However, it has remained unclear in children whether troponin values correlate with CMR evidence of myocardial injury or adverse outcomes [65,66 ▪ ]. Recent data, including children and adults with COVID-19 infection and vaccine-associated myocarditis have shown that higher troponin levels on admission correlate with persistence of myocardial injury on CMR [67 ▪ ].…”
Section: Biomarkers Of Myocarditismentioning
confidence: 99%
“…Based on CDC guidance, troponin elevation is an integral part of the diagnosis of myocarditis and may also be used to chart clinical improvement [64]. However, it has remained unclear in children whether troponin values correlate with CMR evidence of myocardial injury or adverse outcomes [65,66 ▪ ]. Recent data, including children and adults with COVID-19 infection and vaccine-associated myocarditis have shown that higher troponin levels on admission correlate with persistence of myocardial injury on CMR [67 ▪ ].…”
Section: Biomarkers Of Myocarditismentioning
confidence: 99%